Investigating the Relationship between Work-Family Conflict (WFC) and Organizational Intelligence with the Mediating Role of Perceived Organizational Support and Job Performance of Nurses in Golestan Hospital of Ahvaz City, Khuzestan, Iran - Narges Rasouli; Alireza Heidari; Farah Naderi; Fatemeh Sadat Marashian (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Nurses constitute one of the most important occupational groups and pillars in organizations who provide healthcare services in all countries. Objectives: The present study aimed to investigate the relationship between work-family conflict (WFC) and organizational intelligence with the mediating role of perceived organizational support and job performance of nurses. Methods: The statistical population included all the nurses in Golestan hospital of Ahvaz city in 2019, 252 of which were selected as the sample of the study using convenience sampling. The research instruments included Patersonchr('39')s Job Performance Questionnaire, the Work-Family Conﬂict Scale (WAFCS), the Organizational Intelligence Questionnaire, and Survey of Perceived Organizational Support (SPOS). The proposed model was evaluated using path analysis. Results: A direct and negative relationship was observed between work-family conflict and job performance (β= -0.456, P=0.000) and between work-family conflict and perceived organizational support (β= -451, P=0.000). There was a direct and positive relationship between organizational intelligence and perceived organizational support (β=0.289, P=0.000) and between perceived organizational support and job performance (β=0.204, P=0.000). There was no direct and significant relationship between organizational intelligence and job performance among nurses (β=0.092, P=0.120). The path analysis results indicated that perceived organizational support had a mediating role in the relationship between work-family conflict and job performance (β= -0.068, P=0.008) as well as the one between organizational intelligence and job performance (β=0.017, P=0.012). Conclusion: According to the results of this study, the proposed model was appropriate and can be considered as an important step towards identifying the factors affecting the job performance of nurses.